Gamified Health Promotion in Schools: The Integration of Neuropsychological Aspects and CBT—A Systematic Review - Evgenia Gkintoni; Fedra Vantaraki; Charitini Skoulidi; Panagiotis Anastassopoulos; Apostolos Vantarakis (Medicina)
Background and Objectives: This systematic review examines the integration of gamified health promotion strategies in school settings, with a focus on their potential to positively influence health behaviors and promote well-being among adolescents. This study explores the incorporation of cognitive behavioral therapy (CBT), artificial intelligence, and neuropsychological principles in gamified interventions, aiming to enhance engagement and effectiveness. Materials and Methods: A narrative synthesis of 56 studies, following PRISMA guidelines, underscores the significant impact of these gamified interventions on mental health outcomes, emphasizing reductions in anxiety, depression, and burnout while improving coping skills and lifestyle habits. The focus of key areas in mental health outcomes, emotional regulation, cognitive flexibility, and adherence mechanisms is explored through quantitative and qualitative syntheses to underscore intervention effectiveness and design principles. Results: This review highlights the high-quality evidence supporting the use of gamification in educational settings and calls for further research to optimize design elements and address implementation barriers. The findings propose that well-designed gamified health interventions can effectively engage students, promote healthy behaviors, and improve mental well-being while acknowledging the need for further studies to explore underlying mechanisms and long-term effects. Conclusions: Gamified health interventions that embed CBT and neuropsychological principles are promising for promoting the mental well-being of schoolchildren. Although the evidence indicates that they are effective in improving psychological and behavioral outcomes, further research is needed to optimize design features and overcome implementation challenges to ensure wider and more sustainable application.